Intimate partner violence–related experiences and mental health among college students in Japan, Singapore, South Korea and Taiwan. (May 2016) - Kamimura, Akiko; Nourian, Maziar M; Assasnik, Nushean; Franchek-Roa, Kathy
Background: Intimate partner violence (IPV) is a significant public health threat that contributes to a wide range of mental and physical health problems for victims. Aims: The purpose of this study was to examine IPV-related experiences and mental health outcomes among college students in Japan, Singapore, South Korea and Taiwan. Methods: The data were obtained from the Inter-University Consortium for Political and Social Research (ICPSR), the International Dating Violence Study (IDVS) 2001–2006 (ICPSR 29583; N = 981; Japan n = 207; Singapore n = 260; South Korea n = 256; Taiwan n = 258). Results: Co-experience of physical IPV victimization and perpetration was associated with borderline personality traits and posttraumatic stress disorder (PTSD), but not with depression. Childhood sexual abuse, gender hostility and violence socialization were significant predictors of borderline personality traits, depression and PTSD. While country and gender variations in mental health are noted, there are two specific populations that may need special attention for mental health interventions: Taiwanese women especially for borderline personality traits and PTSD, and Japanese men especially for depression. Conclusion: IPV victimization and perpetration, childhood sexual abuse, gender hostility and violence socialization have a significant impact on the mental health of college students in Japan, Singapore, South Korea and Taiwan. Since IPV and mental health are significant public health issues, research on IPV and mental health consequences of IPV victimization and perpetration in these countries should be further expanded in order to better understand the interventions that will be effective in treating victims, perpetrators and victim/perpetrators of IPV.